Etika Bisnis Rasulullah SAW Sebagai Pelaku Usaha Sukses dalam Perspektif Maqashid Syariah - Neni Hardiati (Jurnal Ilmiah Ekonomi Islam, 2021)
This study aims to review the business ethics carried out by Rasulullah SAW in accordance with the objectives of maqashid sharia. The writing of this journal article uses qualitative research, in this article, the literature study conducted by the author is to search various written sources, whether in the form of books, archives, magazines, articles, and journals, or documents relevant to the problem. reviewed from the latest journals that discuss the business ethics carried out by the Prophet Muhammad which is in accordance with the objectives of maqashid sharia. Based on the above discussion, what is obtained is that business actors must follow business ethics as exemplified by the Prophet. However, there are several aspects that must be fulfilled involving some irresponsible parties, such as dishonesty, not protecting consumer rights, friendly buyers or using disrespectful language, buyers who do not protect the rights of patrons, and business actors who are not responsible for customers and pelapak quickly and precisely. The implementation of maqashid sharia, four safeguards of which can protect consumers from their rights. Keywords: Business Ethics, Business Personnel, Perspective, Maqashid Syariah